Hip-Hop Fight Club: Radical Theory, Education, and Practice in and beyond the Classroom - Ball, Jared A. (Radical Teacher, 2013)
Hip-hop remains a viable method for the teaching of radical theory, emancipatory journalism and Africana Media Theory. Fight Club is an emergent model that builds from existing hip-hop traditions of freetyle battling where critical thought and intellectual challenges of hueristic norms are upended. This article argues in favor of bringing the Fight Club model into the classroom which allows for heightened student engagement and the inclusion of radical theoretical approaches to the study of mass media, communication and journalism.